Personality Traits as Markers of Psychosis Risk in Kenya: Assessment of Temperament and Character. Issue 1 (19th September 2020) - Mamah, Daniel; Cloninger, C Robert; Mutiso, Victoria N; Gitonga, Isaiah; Tele, Albert; Ndetei, David M
Abstract: Specific personality traits have been proposed as a schizophrenia-related endophenotype and confirmed in siblings at risk for psychosis. The relationship of temperament and character with psychosis has not been previously investigated in Africa. The study was conducted in Kenya, and involved participants at clinical high-risk (CHR) for psychosis ( n = 268) and controls ( n = 251), aged 15–25 years. CHR status was estimated using the Structured Interview of Psychosis-Risk Syndromes (SIPS) and the Washington Early Psychosis Center Affectivity and Psychosis (WERCAP) Screen. Student's t -tests were used to assess group differences on the Temperament and Character Inventory (TCI). Neurocognitive functioning, stress severity, and substance use were correlated with the TCI, correcting for psychosis severity. CHR participants were more impulsive (ie, higher novelty seeking [NS]) and asocial (ie, lower reward dependence) than controls. They were also more schizotypal (ie, high self-transcendence [ST] and lower self-directedness [SD] and cooperativeness [CO] than controls). CO was related to logical reasoning, abstraction, and verbal memory. Stress severity correlated with high HA and schizotypal character traits. Lifetime tobacco use was related to NS, and lifetime marijuana use to high NS, low SD and high ST. Temperament and character of Kenyan CHR youth is similar to that observed in schizophrenia. Psychosis risk in Kenya is associated with impulsive, asocial, and schizotypal traits. CHR adolescents and young adults with schizophrenia-specific personality traits may be most at risk for developing a psychotic disorder and to require early intervention to improve outcomes.